Keanekaragaman Genetika Pisang Bergenom B Berdasarkan Penanda Mikrosatelit - Windarti Windarti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2009)
The morphology and isozyme marker was not enough to reveal banana genetic diversity. So, it needs molecular analysis. The purpose of this research is to know the genetic diversity of banana with B genome using microsatelite marker. Forty bananas with B genom from Yogyakarta Agriculture Service and Animal Husbandary Service and also from Tropical Fruit Centre of Bogor Agriculture Institute were amplified using 6 loci (MaCIR327b, MaCIR108, Ma-3-139, Ma-3-90, Ma-1-17, and Ma-1-27). The diversity were identified with allele amount, genotype, observe heterozigosity, and filogeny. There are eight allele per locus average from six microsatelites. MaCIR108 produced the highest allele amount, there are 13 alleles. The research identified 75 genotypes. MaCIR327b, MaCIR108, Ma-3-139, Ma-3-90, Ma-1-17, and Ma-1-27, respectively, produced 8, 20, 13, 14, 15, and 5 alleles. The Ho average is quite high, there are 0,77. The similarity coefficient is between 0,597 – 1,00. MaCIR108 and Ma-3-90 can be used to identify banana group genom. As a group genom characteristic, Ma-1-17 needs more research. Identification result between morphology and microsatelite marker were different. Based on morphology marker, Sri Wulan and Byar cultivar were ABB, and Ketip Gunung Sari were AAB, but based on microsatelite marker Sri Wulan and Byar cultivar were AAB, while Ketip Gunung Sari has not B on its genom. Keywords: genetic diversity, banana, microsatelit.